2012
DOI: 10.3389/fphys.2012.00266
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Fluid-Chemical Model Toward Modeling the Formation of Intra-Luminal Thrombus in Abdominal Aortic Aneurysms

Abstract: Abdominal Aortic Aneurysms (AAAs) are frequently characterized by the presence of an Intra-Luminal Thrombus (ILT) known to influence their evolution biochemically and biomechanically. The ILT progression mechanism is still unclear and little is known regarding the impact of the chemical species transported by blood flow on this mechanism. Chemical agonists and antagonists of platelets activation, aggregation, and adhesion and the proteins involved in the coagulation cascade (CC) may play an important role in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 64 publications
2
88
0
1
Order By: Relevance
“…This is supported by multiple anatomic studies of ILT, as it commonly occurs in the distal anterior region of AAA [23,[41][42][43]. In 2012, an integrated fluid-chemical approach for modelling ILT formation in AAA was introduced by Biasetti et al which showed agreement with the site specificity of ILT formation and the movement of vortex structures [44].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This is supported by multiple anatomic studies of ILT, as it commonly occurs in the distal anterior region of AAA [23,[41][42][43]. In 2012, an integrated fluid-chemical approach for modelling ILT formation in AAA was introduced by Biasetti et al which showed agreement with the site specificity of ILT formation and the movement of vortex structures [44].…”
Section: Introductionmentioning
confidence: 65%
“…With this in mind, we approximated the blood flow as laminar and considered the blood to be an incompressible fluid with a density of 1050 kg/m 3 . The walls of the arteries were characterised by no-slip, rigid wall boundary conditions [5,6,32,35,54,55] and the viscosity was modelled using a non-Newtonian approximation (Carreau-Yasuda, as implemented by Biasetti et al [44]; [56]). By using a non-Newtonian model, as opposed Newtonian, we can capture the macro-scale shear-thinning of the blood, allowing a one-way Lagrangian particle transport model to provide a good prediction of individual blood-cell trajectories within the continuous phase (blood).…”
Section: Physical Assumptions and Boundary Conditionsmentioning
confidence: 99%
“…For the modeling of blood coagulation and thrombus formation in the infarcted LV, we adopt thrombosis biochemical reaction models employed in previous studies (4,28,32) of vascular thrombosis. It is assumed here that thrombus formation in the LVs with AMI is initiated by the exposure of blood to tissue factor (TF) (42) emanating from the damaged ventricle wall.…”
Section: Methodsmentioning
confidence: 99%
“…2) is coupled with the hemodynamic simulation through the flow velocity vector ¡ U. The diffusion coefficient D for the coagulation factors is set to 1.0e-8 m 2 /s following Biasetti et al (4). The detailed description of the reaction term R i and the initial concentrations of the species are given in APPENDIX C. At the wall, a zero diffusive flux boundary condition is applied except in the damaged region, where the TF is exposed and combined with factor VIIa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation